2007
DOI: 10.1093/nar/gkl959
|View full text |Cite
|
Sign up to set email alerts
|

The CATH domain structure database: new protocols and classification levels give a more comprehensive resource for exploring evolution

Abstract: We report the latest release (version 3.0) of the CATH protein domain database (). There has been a 20% increase in the number of structural domains classified in CATH, up to 86 151 domains. Release 3.0 comprises 1110 fold groups and 2147 homologous superfamilies. To cope with the increases in diverse structural homologues being determined by the structural genomics initiatives, more sensitive methods have been developed for identifying boundaries in multi-domain proteins and for recognising homologues. The CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
254
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(258 citation statements)
references
References 24 publications
1
254
0
3
Order By: Relevance
“…To investigate the molecular function of AtTLP18.3 from the resolved structure, we submitted the coordinates of AtTLP18.3 to the CATH server (Kawabata, 2003;Greene et al, 2007) to reveal its structure classification. The results indicated that the folding of AtTLP18.3 belongs to a Rossmann fold (CATH code 3.40.50) with an architecture of a three-layer (aba) sandwich.…”
Section: Structure Comparison Suggests That Attlp183 Functions As a mentioning
confidence: 99%
“…To investigate the molecular function of AtTLP18.3 from the resolved structure, we submitted the coordinates of AtTLP18.3 to the CATH server (Kawabata, 2003;Greene et al, 2007) to reveal its structure classification. The results indicated that the folding of AtTLP18.3 belongs to a Rossmann fold (CATH code 3.40.50) with an architecture of a three-layer (aba) sandwich.…”
Section: Structure Comparison Suggests That Attlp183 Functions As a mentioning
confidence: 99%
“…Protein classification could be an illustrative example to show the needs. A major goal of SCOP (structural classification of proteins) 8 and CATH (class, architecture, topology, homologous superfamily) 9 is to understand the structural, functional, and evolutionary relationships among proteins by classifying domains according to their structure. This structure-based approach may be effective in detecting distant relationships across proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The CATH database [4] was filtered to select superfamilies with (a) more than 20 sequence diverse relatives (sequence identity lower than 35%), (b) at least 3 different EC numbers (down to the 3rd level), and (c) structures solved as part of the Protein Structure Initiative and in particular the Midwest Center for Structural Genomics (MCSG) with which we collaborate directly. We then manually checked the set of superfamilies thus selected, to further restrict our analysis to 3 superfamilies with a wide range of molecular functions: the HUP domain superfamily (CATH 3.40.50.620) that was chosen because it is very ancient and presents a particularly striking diversity of entirely unrelated functions; the HAD superfamily (CATH 3.40.50.1000) that was chosen as one of the superfamilies considered in the above mentioned SFLD; and the PBP like superfamily (CATH 3.40.190.10) that we selected to study function diversity in a superfamily that includes many non enzymatic functions.…”
Section: Resultsmentioning
confidence: 99%